Long-Term Variability of the East Sea Intermediate Water Thickness: Regime Shift of Intermediate Layer in the Mid-1990s - Park, JongJin (Frontiers in Marine Science, 2022)
The shipboard measurements over approximately 55 years in the southwestern part of the East Sea (Sea of Japan) demonstrate a remarkable basin-wide, interannual-interdecadal variability in the temperature-based thickness of the East Sea Intermediate Water (ESIW) whose temporal variability shows strong correlation with the density-based thickness (r = 0.97). Relevant to the long-term variability of the ESIW thickness, clear changes in horizonal and vertical features have been observed at the intermediate layer in the mid-1990s, such as (1) increases in vertical temperature gradient in the thermocline by shoaling of 2–5°C isotherms, (2) relatively high correlations among isotherms in the inter-decadal timescale, (3) appearance of zonal phase difference in the ESIW thickness variability after the mid-1990s, and (4) correlation phase change between Arctic Oscillation Index and ESIW thickness. The ESIW thickness could be smaller when its formation is weaker, and when the formation of deep-water mass below it becomes stronger. Based on the features observed, we hypothesized on the regime shift concerning the East Sea meridional overturning circulation; before the mid-1990s, active deep-water formation mainly controlled the ESIW-layer variability, but after the mid-1990s, the ESIW formation rate predominantly affected its own thickness variability.